Role of drugs in traffic accidents. Issue 6251 (15th November 1980) - Honkanen, R; Ertama, L; Linnoila, M; Alha, A; Lukkari, I; Karlsson, M; Kiviluoto, O; Puro, M
Abstract : Serum samples from 201 drivers who presented at emergency departments within six hours after being injured in a road accident and 325 control drivers selected randomly at petrol stations were screened for drugs by combined thin-layer and gas chromatography. Blood alcohol concentrations were also measured, and a questionnaire on the subjects' state of health and use of drugs administered. At interview 30 patients (15%) and 44 controls (13%) said that they had taken drugs in the previous 24 hours. Four patients (2%) and six controls (2%) said that they had taken psychotropic drugs, but serum analysis detected psychotropic drugs in 10 patients (5%) and eight controls (2.5%). Diazepam was found in 16 of the 18 subjects in whom psychotropic drugs were detected. Alcohol was detected in 30 patients (15%) and three controls (1%). Drug use appeared to be somewhat lower in Finland than in other Western countries, and illness to be a more important traffic hazard than drugs in general. Interview was not a reliable method of establishing whether drivers had taken psychotropic drugs. Taking diazepam may increase the risk of being involved in a traffic accident, but alcohol was the most powerful risk factor.